Some aspects of the EAEU digital trade in the foreign policy of the Republic of Kazakhstan - Makasheva, K.; Patnaik, A.; Mukhtarova, K.; Konuspayev, Ye. (KU Publ., 2022)
The paper presents the main factors of the development of digital integration in the field of trade and ec onomic relations in the foreign policy of Kazakhstan within the framework of the Eurasian Economic Union (EAEU). The authors discuss the importance of developing international relations with partner countries and key documents for establishing relations. Paper highlights the reasons for the low dynamics of processes for building ways of developing digital trade in the EAEU. The authors provide a review of the regulatory framework for the development of digital trading platforms, as well as an analysis of current trends in the framework of this issue. An important aspect of the study was the problem of digitalization in the field of regulation of conditions for the EAEU member countries as players in the digital trading ecosystem; analysis of transnational interactions between participants in the integration process. The paper discusses the promising directions of development of trade and economic relations in the digital economy, identifies the key problems that are important for their further solution to improve the effectiveness of r elations between Kazakhstan and the participants of the integration union.
Қазақстан Республикасының сыртқы саясатындағы ЕАЭО цифрлық саудасының кейбір аспектілері
О некоторых аспектах цифровой торговли ЕАЭС во внешней политике Республики Казахстан
Keywords: integration union; digital integration; digital trade; digital market ecosystem; regulation of ec onomic integration processes; digital technologies; information space; participants in the digital ecosystem; Kazakhstan’s foreign policy